Cisplatin-Membrane Interactions and Their Influence on Platinum Complexes Activity and Toxicity - Martinho, Nuno; Santos, Tânia C. B.; Florindo, Helena F.; Silva, Liana C. (Frontiers in Physiology, 2019)
Cisplatin and other platinum(II) analogues are widely used in clinical practice as anti-cancer drugs for a wide range of tumours. The primary mechanism by which they exert their action is through the formation of adducts with genomic DNA. However, multiple cellular targets by platinum(II) complexes have been described. In addition, the early events occurring at the plasma membrane, i.e., platinum-membrane interactions, seem to be involved in the uptake, cytotoxicity and cell-resistance to cisplatin. In fact, plasma membrane influences signalling events, and cisplatin-induced changes on membrane organization and fluidity were shown to activate apoptotic pathways. This review critically discusses the sequence of events caused by lipid membrane-platinum interactions, with emphasis on the mechanisms that lead to changes in the biophysical properties of the membranes (e.g. fluidity and permeability), and how these correlate with sensitivity and resistance phenotypes of cells to platinum(II) complexes.